Review paperAetiology of acne vulgaris – review of present literature - Bergler-Czop, Beata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Acne vulgaris is the most common dermatosis found in patients between 11 and 30 years of age. It is believed that acne effects up to 80% of persons from this age group, or taking into account its mild forms, even 100% of persons from this age group. Ninety-five percent of the changes occur on the face and on the upper part of the trunk, rarely on the other parts of the body, and because of this location and its chronic character, this disease frequently constitutes a serious psychological problem for a patient. The microcomedone is the primary change which starts the whole inflammatory cascade. Microcomedones may have different causes, such as: linolenic acid deficiency, excessive secretion of androgens, or excess of free fatty acids. This is accompanied by excessive production of tonofilaments, desmosomes and keratins. This process leads to narrowing of the follicle opening and impedes removal of the sebaceous gland contents onto the skin surface. Pro-inflammatory cytokines, mainly IL-1, are also involved in the keratinisation process. Microcomedones are colonised mainly by an anaerobic bacterium – Propionibacterium acnes.